2019
DOI: 10.1088/1757-899x/529/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

On modelling viscoplastic behavior of the solidifying shell in the funnel-type continuous casting mold

Abstract: As it is known from literature, the metals tend to follow a viscoplastic law at high temperatures. Thereby, based on the authors’ previous developments to simulate the behavior of the equiaxed crystals packed bed, a viscoplastic stress model is applied to the thin slab casting process. The model is reduced to the single phase mixture formulation for faster and robust simulations. In this idea, the solidifying shell represents a ‘creeping solid’ and the Norton-Hoff type stress model is formulated with the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Further details on that research field can be found in ref. [26][27][28][29][30][31][32][33][34][35].…”
Section: Steel Continuous Casting: Solidification Flow and Magnetohydrodynamicsmentioning
confidence: 99%
“…Further details on that research field can be found in ref. [26][27][28][29][30][31][32][33][34][35].…”
Section: Steel Continuous Casting: Solidification Flow and Magnetohydrodynamicsmentioning
confidence: 99%
“…First, the averaged ratio between the liquid and solid electric conductivities is plotted in Figure 16(a) in the left curve, which is derived here from the extended data for different AISI steel grades, reported in 1978 by Chu and Ho. [44] The right curve in Figure 16(a) shows slab surface temperature along the mold's wide face, simulated by Vakhrushev et al [45,46] The corresponding thickness (100 pct of solid, top picture) and the conductance ratio (bottom picture) of the solid shell are plotted in Figure 16(b), which are obtained from the thin slab simulations [45,46] and calculated for the 72-mm-thick slab using Eq. [19] based on the temperature-dependent electric conductivity (see Figure 16(a)).…”
Section: Application To Continuous Castingmentioning
confidence: 99%
“…[Chu & Ho 1978] wide face m m Fig. 16-Solid shell conductance ratio for the thin slab casting: (a) averaged temperature-dependent ratio r sol =r liq (from Chu and Ho 1978) [44] and surface temperature T surf for the 72-mm-thin slab (Vakhrushev et al); [45,46] (b) simulated shell thickness (top); and its conductance ratio (bottom).…”
Section: (A) (B)mentioning
confidence: 99%
“…Several numerical models have been developed for the contact problem and air gap formation [20][21][22][23]. Deformation models coupled with the fluid flow, heat transfer, and solidification have been described elsewhere [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%